The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ar.24038
|View full text |Cite
|
Sign up to set email alerts
|

Skull Morphology of the Lizard Ptychoglossus vallensis (Squamata: Alopoglossidae) With Comments on the Variation Within Gymnophthalmoidea

Abstract: In recent years, major changes have been proposed for the phylogenetic relationships within the Gymnophthalmoidea, including the description of Alopoglossidae. Recent studies relied primarily on molecular data and have not accounted for evidence from alternative sources, such as morphology. In this study, we provide a detailed bone‐by‐bone description of the skull of Ptychoglossus vallensis and compare this species with other gymnophthalmoideans. The description was based on 10 cleared‐and‐stained specimens, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…The occiput in miniaturized gymnophthalmoideans is globular and not covered by the parietal, having a bulging occipital condyle (Fig. A–C; Hernández Morales et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occiput in miniaturized gymnophthalmoideans is globular and not covered by the parietal, having a bulging occipital condyle (Fig. A–C; Hernández Morales et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Calyptommatus leiolepis contains all representative characters of gymnophthalmids: fused frontals, loss of a parietal foramen, and frontal lappets covering the parietal (Estes et al, ; Bell et al, ). Although these characters are common to gymnophthalmids, there is a large amount of variation within the group and these are also found in Alopoglossidae (Hernández Morales et al, ). Much of the variation within gymnophthalmids is found in the temporal and suborbital fenestrae, frontal, parietal, squamosal, palatal elements, presence or absence of lacrimals, postfrontals, postorbitals, tooth counts, and morphology of the jaw and braincase (Bell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In part, that is because methods for integrating polymorphic characters into phylogenetic analyses are not straightforward. Nevertheless, continued investigations into morphological variation have yielded new insights into phylogenetic relationships and morphological evolution of squamates (e.g., Bhullar, 2011 ; Čerňanský, Smith & Klembara, 2014 ; Díaz-Fernández, Quinteros & Lobo, 2017 ; Stilson, Bell & Mead, 2017 ; Hernández Morales et al, 2019 ). Investigations into other vertebrate clades including turtles ( Joyce & Bell, 2004 ), frogs ( Bever, 2005 ), birds ( Kirchner-Smith, 2015 ), and mammals ( Gould, 2001 ) have also shown that substantial amounts of previously unreported morphological variation exist, some of which alter the diagnostic utility of previously reported features.…”
Section: Discussionmentioning
confidence: 99%
“…Members of Alopoglossus (=Alopoglossidae) can be distinguished from other gymnophthalmoids by: (i) having the tongue entirely covered by oblique plicae (only partially covered by oblique plicae or covered with scale‐like papillae in other gymnophthalmoids); (ii) cristae cranii of the frontal forming a tubular structure (flanged in Gymnophthalmus and Heterodactylus ); (iii) the presence of postorbitofrontal (also present in Calyptommatus , Dryadosaura , Anotosaura , Colobosauroides , Ameiva , Cnemidophorus , Dicrodon , Dracaena , Kentropyx and Teius ); (iv) the borders of the palatine process curved divergently and its distal tip truncated (in other Gymnophthalmoidea, this process has convergent or parallel borders according to Hernández‐Morales et al, ); and (v) hemipenis without mineralized structures (Teiidae shows the same condition but most gymnophthalmids have mineralized structures in their hemipenis).…”
Section: Discussionmentioning
confidence: 99%